Evolving standards of care in advanced gastric cancer. (December 2011) - Kurtz, Jean-Emmanuel; Dufour, Patrick
Despite its decreasing incidence in western countries, the care of gastric cancer remains a concern, as many patients are diagnosed with advanced disease. Whereas localized gastric cancer has benefited from advances in surgical management and perioperative chemotherapy, patients with unresectable or metastatic disease have a poor prognosis. However, advances in chemotherapy have still arisen, with the onset of more convenient and active schedules of treatment, but no significant breakthrough has been achieved in terms of survival. Recent trials in advanced gastric cancer have been focusing on targeted therapies. This article aims to focus on the current state of the art in terms of chemotherapy for advanced gastric cancer, as well as to describe and explain the rationale and hopes for newer therapies that are currently under investigation.